America's last great newspaper war : the death of print in a two-tabloid town - Jaccarino, Mike (Empire State Editions, an imprint of Fordham University Press, 2020)
Recounts the story of America's last great newspaper war between the New York Daily News and the New York Post, as both papers' long rivalry turned existential amid the rise of digital news. The story is told through the eyes of the reporters, or ""runners, "" and photographers who fought the war on the ground in cities across America.